EFFECTIVENESS OF ASCORBIC ACID AS A NATURAL SUBSTITUTE FOR CARBON MONOXIDE IN MAINTAINING THE QUALITY OF GOLDBANDED JOBFISH FILLETS - Novie Wijaya; Rafi Ohorella; Alwi Mulato; Meilya Suzan Triyastuti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2026)
The use of carbon monoxide (CO) in the fishing industry to improve the bright red color of fish fillets has been controversial. Despite its effectiveness and buyer demand, CO results in food safety risks and there are strict regulations in some countries. The objective of this study was to examine the effectiveness of ascorbic acid as a substitute for CO to enable products to penetrate the European Union market. The research method employed was a combination of organoleptic and microbiological testing of Goldbanded Jobfish fillets treated with CO, whereas treatment with ascorbic acid was only evaluated through organoleptic testing. The results showed that the use of CO in Goldbanded jobfish fillets resulted in bright red color and a soft texture. However, European countries prohibit the injection of CO in meat products, so the fisheries industry cannot export Goldbanded jobfish (Pristipomoides multidens) fish fillets to the European Union. Therefore, innovation in natural ingredients is needed to maintain the red color of fish fillets. The addition of 0.03% ascorbic acid, can maintain the bright red color of fish fillets and produce a firm and dense texture. To our knowledge, this research is the latest alternative solution to replace CO gas adjuvant in improving the texture of frozen Goldbanded jobfish products.